Global food system emissions could preclude achieving the 1.5° and 2°C climate change targets - Clark, MA; Lynch, J; Domingo, N; Colgan, K; Thakrar, S; Hill, J; Tilman, D; Azevedo, I (American Association for the Advancement of Science, 2020)
The Paris Agreement’s goal of limiting the increase in global temperature to 1.5° or 2°C above preindustrial levels requires rapid reductions in greenhouse gas emissions. Although reducing emissions from fossil fuels is essential for meeting this goal, other sources of emissions may also preclude its attainment. We show that even if fossil fuel emissions were immediately halted, current trends in global food systems would prevent the achievement of the 1.5°C target and, by the end of the century, threaten the achievement of the 2°C target. Meeting the 1.5°C target requires rapid and ambitious changes to food systems as well as to all nonfood sectors. The 2°C target could be achieved with less-ambitious changes to food systems, but only if fossil fuel and other nonfood emissions are eliminated soon.